Attracting Private Investment through Power Sector Reforms - Rehermann, Thomas (International Finance Corporation, Washington, DC, 2018)
Private sector investment is much needed in emerging markets to upgrade energy supplies, but too often power utilities in these markets are uncompetitive. In order to attract private investment, many aspects of how power utilities are operated need to be reformed. With their experience in helping to structure and finance successful infrastructure projects in emerging markets, development finance institutions are well positioned to support emerging market government efforts to translate power sector reforms into private investment. Public utilities in emerging markets are often uncompetitive, creating a drag on economic growth and development. Public sector reform, however, can create the enabling environment needed to attract much needed private sector investment to energy projects. IFC projects in the Philippines and Pakistan demonstrate how development institutions can play a role in spurring reform and bringing in private capital.